Mendelian and polygenic inheritance of intelligence: A common set of causal genes? Using next-generation sequencing to examine the effects of 168 intellectual disability genes on normal-range intelligence - Franić, Sanja; Dolan, Conor V.; Broxholme, John; Hu, Hao; Zemojtel, Tomasz; Davies, Garreth E.; Nelson, Kelly A.; Ehli, Erik A.; Pool, René; Hottenga, Jouke-Jan; Ropers, H.-Hilger; Boomsma, Dorret I. (Intelligence (Norwood), 2015)
Despite twin and family studies having demonstrated a substantial heritability of individual differences in intelligence, no genetic variants have been robustly associated with normal-range intelligence to date. This is largely ascribed to the high polygenicity of intelligence, i.e., to its being subject to the effects of a large number of genes of individually small effect. Intellectual disability, on the other hand, frequently involves large effects of single genetic mutations, many of which have been identified. The present paper aims to 1) introduce the reader to the current state of genetic intelligence research, including next-generation sequencing and the analysis of rare genetic variants, and 2) examine the possible effects of known disability genes on normal-range intelligence. The rationale for the latter rests on the fact that genetic variants affecting continuous, polygenic traits are often concentrated in the same areas of the genome as those underlying related monogenic phenotypes. Using an existing pool of known intellectual disability genes, we constructed a set of 168 candidate genes for normal-range intelligence, and tested their association with intelligence in 191 individuals (aged 5–18) sampled from the high and low ends of the IQ distribution. In particular, we 1) employed exon sequencing to examine the possible effects of rare genetic variants in the 168 genes, and 2) used polygenic prediction to examine the overall effect of common genetic variants in the candidate gene set in a larger sample (N=2125, mean age 20.4, SD=14.1). No significant association between the candidate gene set and intelligence was detected. •To date, no genetic variants have been robustly associated with intelligence.•In contrast, many genes for intellectual disability (ID) have been identified.•We hypothesize that ID genes may be enriched with genetic variants associated with intelligence.•To this end, we test for an association between intelligence and 168 known ID genes.•No association is detected.